Physical Games as a Learning Medium for Early Childhood to Improve Gender-Responsive Education - Rita Nofianti; Nurhalimah Tambunan; Anggun Febri Purwanti (International Journal of Society and Law, 2025)
Gender-responsive education in early childhood is a crucial aspect in shaping equal understanding of gender roles in society. Research shows that even before the age of three, children begin to acquire cultural gender stereotypes through their interactions with adults and peers, and by the age of six, children have already formed gender biases regarding intelligence and expected roles of boys and girls. This study examines the role of physical games as an effective learning medium to introduce gender-responsive concepts to early childhood (ages 4–6). Using a mixed-method approach with a pre-post intervention design, the study involved 75 children across 4 early childhood education institutions over 16 weeks. The results indicate that physical games designed with gender-responsive principles significantly improve children’s understanding of role equality (p < 0.05), reduce gender stereotypes by 41%, and foster inclusive social skills. These findings align with the need to provide inclusive physical activity opportunities that accommodate children’s factors such as self-esteem, cultural beliefs, ability levels, peer evaluation, and gender diversity. This research provides important contributions to the development of a more inclusive and gender-responsive early childhood education curriculum..